Regional Economic Outlook, October 2009, Europe : Securing Recovery. (Regional Economic Outlook, 2009)
Europe's contraction is ending, but the recovery is fragile. Policymakers should look beyond the crisis to secure a durable upswing and address the threats to potential growth from the crisis and the continent's well-known structural rigidities. The report's analytical work stresses the uncertainty surrounding potential growth estimates, and the more volatile environment faced by emerging economies in a tightly integrated region. In the near term, this calls for measures to restore the financial sector to health and for continued macroeconomic support, while preparing for the exit from extraordinary interventions in a coordinated and transparent fashion. Higher longer-term growth through structural change will support the recovery, smooth the exit, and help emerging markets to adjust to lower capital inflows in the crisis' aftermath. Published biannually in May and October.